2016
DOI: 10.1007/s00540-016-2195-0
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane anesthetic preconditioning protects the lung endothelial glycocalyx from ischemia reperfusion injury in an experimental lung autotransplant model

Abstract: Sevoflurane preconditioning protects pulmonary glycocalyx and reduces expression of leukocyte chemokines in an in-vivo model of pulmonary IR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 39 publications
2
32
1
1
Order By: Relevance
“…There are conflicting reports of protective and deleterious effects of propofol in healthy and diseased lungs . Our findings indicated no change in PFT in infant baboons after administration of a relatively large dose of propofol.…”
Section: Discussioncontrasting
confidence: 57%
“…There are conflicting reports of protective and deleterious effects of propofol in healthy and diseased lungs . Our findings indicated no change in PFT in infant baboons after administration of a relatively large dose of propofol.…”
Section: Discussioncontrasting
confidence: 57%
“…25 These data are corroborated by others, for example, Casanova et al reported an efficacy of Sevo preconditioning in an autotransplant pig model showing a decrease of oxidative stress, proinflammatory mediators, chemokines, and adhesion molecules. 9,15 Also, a study of Rancan et al in lung autotransplant in pigs showed decreased inflammatory cytokine and chemokine levels in the liver. 26 Although there is some evidence of an amelioration of PGD in Syn lung Tx, no reports are available so far on allo-Tx in the context of Sevo preconditioning.…”
Section: Discussionmentioning
confidence: 99%
“…11,13 Some data exist for Sevo preconditioning in lung Tx, but they are largely limited to the analysis of PGD, showing a decrease of the inflammatory response and oxidative stress of I/R injury. 9,15 Others demonstrated the efficacy of volatile anesthetics to attenuate I/R injury in an isolated lung model without Tx procedure. 16,17 We therefore investigated here if Sevo preconditioning of the donor graft might have protective effects on both, PGD and AR.…”
Section: Introductionmentioning
confidence: 99%
“…In previous human studies or animal experiments, we measured the damage of EGL resulting from cardiac surgery, trauma patients or transplantation through blood sampling, and the authors also measured this using blood sampling. The most accurate method was to use bronchoalveolarlavage, but it was not appropriate in patients with pulmonary resection and could not be selected (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%